2004
DOI: 10.1097/01.smj.0000078681.07409.f7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Postdural Puncture Headache and Backache, and Success Rate of Dural Puncture: Comparison of Two Spinal Needle Designs

Abstract: The low complication and failure rates make these two types of smaller size spinal needle design good candidates for dural puncture procedures, such as spinal anesthesia, diagnostic lumbar punctures, and myelograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Thicker needles cause greater trauma and more inflammation in the tissue, resulting in more PDPB (15). However, some studies have shown no difference in PDPB related to the needle size and shape (7,11). The second hypothesis is that repeated spinal puncture attempts cause PDPB (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thicker needles cause greater trauma and more inflammation in the tissue, resulting in more PDPB (15). However, some studies have shown no difference in PDPB related to the needle size and shape (7,11). The second hypothesis is that repeated spinal puncture attempts cause PDPB (16).…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al (15) found no difference in PDPB related to the number of redirections of the spinal needle. Pan et al (7) found no difference in PDPB related to the number of attempts of spinal puncture. The Atraucan spinal needle is used with an introducer that is quite thicker than the subarachnoid needle itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 More recent studies on back pain after spinal anesthesia have reported the incidence to be 10% to 29% (Table 4). [43][44][45] One study noted the backaches to be mild in intensity, characterized by local tenderness at the site of injection, and responded to oral anti-inflammatory drugs or resolved spontaneously. 44 The exact duration of the back pain was not noted.…”
Section: Incidence Of Back Pain After Neuraxial Anesthesia: Preexistimentioning
confidence: 98%
“…The incidence of PDPH is directly related to the needle size (gauge) and tip configuration that punctures the dura mater [11,12 ]. Smaller gauge needles with atraumatic, pencil point (non-cutting) tips decrease the risk of PDPH [12 ].…”
Section: Postdural Puncture Headachementioning
confidence: 99%